Don Kalmyk Song Recordings Made by A. M. Listopadov - B. Kh. Borlykova; B. V. Menyaev (Научный диалог, 2022)
In spite of the previous two centuries of recording Kalmyk song folklore there are still unknown and littleknown manuscripts and audio recordings of Kalmyk song art, stored in Russian and foreign archives. The Institute of Russian Literature (Pushkin House) of the Russian Academy of Sciences has a handwritten collection of Don Kalmyk songs, recorded by musicologist Alexander Mikhailovich Listopadov in 1902 in the village of the Denisov Region of the Don Cossack Army. The first section of the manuscript contains seventeen songs and one excerpt from the heroic epic “Dzhangar”, the second section contains eleven songs of the Soviet period and two dance melodies. The records presented in the manuscript are valuable because they are the earliest examples of phonographic records of Kalmyk folklore. A preliminary review of the texts of Kalmyk songs from the first section of A. M. Listopadov revealed that the real collection seems to be extremely heterogeneous, it includes rare examples of hymn, historical, hunting, wedding and lyrical Kalmyk folk songs. Among the texts of the songs, the authors of the article found an excerpt from the epic “Dzhangar”, which refers to the Maloderbet cycle. Introducing the entire collection of A. M. Listopadov into scientific circulation will deepen understanding the Kalmyk folklore of the 19th — the first half of the 20th centuries, will serve as an additional source for its new interpretation, will contribute to comparative studies of the folklore of the Mongolianspeaking peoples.